Pregnancy Outcomes in Patients After Completion of the mRNA Coronavirus Disease 2019 (COVID-19) Vaccination Series Compared With Unvaccinated Patients. Issue 3 (2nd March 2023) - Morgan, John A.; Biggio, Joseph R.; Martin, Jane K.; Mussarat, Naiha; Elmayan, Ardem; Chawla, Harsheen K.; Kandalaft, Savannah; Magalski, Gabrielle R.; Puri, Priya; Williams, Frank B.
Abstract : Vaccination with the two-dose coronavirus disease 2019 (COVID-19) series is associated with lower rates of several adverse pregnancy outcomes. Abstract : OBJECTIVE: To compare frequency of perinatal death between pregnant patients who completed the mRNA coronavirus disease 2019 (COVID-19) vaccination series and unvaccinated patients. METHODS: This retrospective cohort study included 15, 865 pregnant patients who delivered 16, 132 newborns after 20 weeks of gestation within a large regional health system between January 1, 2021, and December 31, 2021. Patients who received two doses of mRNA vaccine (Pfizer–BioNTech [BNT162b2] or Moderna [mRNA-1273]) were included in the vaccinated group and were compared with unvaccinated patients. Exclusions included partial vaccination, viral-vector vaccine, major congenital anomalies, and higher-order multiple gestation. Our primary outcome was perinatal death, including stillbirth and neonatal death, which was evaluated by logistic regression. Unadjusted odds ratios and adjusted odds ratios (aORs) were reported, controlling for age, body mass index (BMI), diabetes, hypertension, smoking, twin gestation, and insurance status. Propensity score matching was also performed. RESULTS: A total of 15, 865 patients were included in the final analysis: 2, 069 in the vaccination group and 13, 796 in the control group. Only 13.0% of the cohort was included in the vaccination group; however, the vaccination rate increased over the course of the study period as the vaccine became more widely available and accepted. Vaccinated patients were older, with higher rates of people of non-Black racial non-Hispanic ethnic backgrounds, people with private insurance, and those with higher BMIs. Vaccination was associated with a lower incidence of perinatal death (0.5% vaccinated group vs 0.8% unvaccinated group, aOR 0.20 0.05–0.88). Vaccination against COVID-19 was also associated with lower rates of preterm delivery (aOR 0.63, 0.48–0.82), neonates with very low birth weight (aOR 0.35, 0.15–0.84), and neonatal intensive care unit (NICU) admission (aOR 0.66, 0.52–0.85). The association between vaccination and lower rates of perinatal death was no longer significant after propensity score matching. CONCLUSION: In a large retrospective cohort study, receipt of the primary mRNA COVID-19 vaccination series was associated with a lower rate of several adverse pregnancy outcomes, including perinatal death, preterm delivery, neonates with very low birth weight, and NICU admission. Although the decreased rates of perinatal death did not remain significant after propensity score matching, there was evidence of directional benefit for vaccinated patients.